Analysis of Symbolic Interaction between Teachers and Deaf Students: Opportunities and Inhibiting Factors - Wijayanti, Rani Ika; Eneng Tika Rostika (Ilmu Inovasi Nusantara, 2023)
This Study delves into the intricate realm of symbolic interactions between teachers and deaf students at SLB Laskar Putra Mandiri Darma-Indonesia, aiming to comprehend the dynamics during the learning process through verbal and non-verbal communication. Employing a purposive sampling technique with a snowball sampling approach, the study uncovers the keys to symbolic interaction encompassing the mind, self, and society. The classification of these keys reveals discernible opportunities and inhibiting factors that significantly impact the success of symbolic interactions. Through interviews and observations, the research not only unravels the complexities of these interactions but also provides recommendations. Educators and institutions are urged to create inclusive environments, offering targeted training programs to enhance teacher proficiency in facilitating effective interactions with deaf students. Identifying and mitigating inhibiting factors, such as communication barriers, emerges as a crucial step toward fostering successful symbolic interactions within the special education context, ultimately contributing to a more inclusive educational landscape